A novel composite calculation model for power coefficient and flapping moment coefficient of wind turbine. (1st May 2017) - Peng, Chao; Zou, Jianxiao; Li, Yan; Xu, Hongbing; Li, Liying
Abstract: In recent years, with continuous increasing capacity of wind turbine, mechanical fatigue problems caused by the vibration of load on wind turbine have become more and more serious. The load is composed mainly by oscillating load and flapping load, which can be measured by power coefficient and flapping moment coefficient. Both of them are important for wind turbine load analysis and operational control to reduce these load vibration. The existing calculation models for wind turbine load only focus on the power coefficient and always neglect flapping moment coefficient. In this paper, a novel composite power coefficient and flapping moment coefficient calculation model based on Blade Element Momentum Theory is proposed. A modified Blade Element Momentum model is built to calculate axial induction factor, tangent induction factor and torque force coefficient of wind turbine. By using them, a new calculation model for power coefficient and flapping moment coefficient is presented. Then, a composite calculation model based on iteration procedure and nonlinear fitting is built for calculating power coefficient and flapping moment coefficient simultaneously. Finally, the proposed calculation model is implemented to calculate the power coefficient and flapping moment coefficient of NREL 5 MW wind turbine and the results demonstrate its effectiveness. Highlights: A novel composite calculation model for power and flapping moment is proposed. The power coefficient and flapping moment coefficient calculation are combined. A modified Blade Element Momentum model is presented. An iteration procedure is designed to calculate induction factors. Nonlinear fitting is used to obtained the composite calculation model.